Anti-Interleukin-1 Agents in Adult Onset Still's Disease - Cecilia Giampietro; Bruno Fautrel (International Journal of Inflammation)
Interleukin 1β (IL-1β) is emerging as a master mediator of adult onset Still’s disease (AOSD) pathogenesis. This pleiotropic cytokine, whose expression is under the control of the inflammasome pathway, has a wide type of effects. As a key mediator of innate immunity is a potent pyrogen and facilitates neutrophilic proliferation and diapedesis into the inflamed tissues, which are key AOSD manifestations. The study of proinflammatory cytokines profiles in sera and pathological tissues of AOSD patients has shown elevated levels of IL-1β, these levels being highly correlated with disease activity and severity. These experimental evidences and the analogy with other autoinflammatory diseases that share with AOSD clinical and biological characteristics have suggested the blockade of IL-1β as a possible new therapeutic option for the AOSD, especially in conventional therapy resistant cases. Anakinra, the first anti-IL-1 agent put on the market, has demonstrated capable to induce a rapid response sustained over time, especially in systemic forms, where anti-TNFα failed to control symptoms. While a growing number of evidences supports the utilisation of anakinra in AOSD, a new generation of anti-IL1β antagonists is developing. Canakinumab and rilonacept, thanks to their higher affinity and longer half-life, could improve the management of this invalidating disease.